BREAKING GENDER STEREOTYPES IN “BABY BLUES” MOVIE - Iduwan; Rullyanti, Merry; Astuty , Lina Tri (Yayasan Darusssalam Bengkulu, 2021)
Gender stereotyping is one of the undeniable facts of life. Gender stereotyping in movies is worth analyzing, since movies can have a significant impact towards the audiences. The objectives of this research were to find out the gender stereotypes of the main characters shown in “Baby Blues” Movie and to know the main characters break the gender stereotypes in Baby Blues movie. This study employed a qualitative descriptive method as research design aiming at collecting the data. Baby Blues movie was chosen as the object of this study. In this case, the researcher analyzed the breaking gender stereotypes of each character represented in this movie. The instrument used in this research was observation checklist and note taking. The note taking is developed by Evans and Davies (2009) theory. There were two findings of this research; (1) It is found that the gender stereotypes of the main characters such as Dika and Dinda consist of four aspect. Dika as a male has physical appearance (having a tall body, having muscular body, wearing shirt, t-shirt, and pant, having short hair, having mustache, strong body), Occupation as a waiter in a restaurant, personality traits (more dominant, emotionally stable, assertive), and Domestic Behavior (take care of finances and playing games). Moreover, Dinda as a female has physical appearance (having thin body, wearing dress, having long hair, beautiful and cute), Occupation as a housewife, personality traits (gentleness, warmth, being emotional, sensitivity), and Domestic Behavior (take care her children, clean the home, take care her husband); (2) On the otherhand, in the meantime, the main characters also break the gender stereotypes. Dika and Dinda break the gender stereotypes for personality traits and domestic behaviors. However, they still had similar physical appearance before the exchange happened. For personality traits, Dika was being gentleness, warmth, emotional, sensitivity, talk active, coward, and feminine. While Dinda was being more dominant, emotionally stable, assertive, lazy, rude, and manly. Moreover, for domestic behavior, Dika was being take care her children, clean the home, and take care her wife, while Dinda was being take care of finances and playing games.